Behavioral economics empowering youth to make smart choices - Wasserman, Jim 1961-; Wasserman, Jiab (Rowman & Littlefield, 2024)
To help empower children to be resilient and have more self-guidance in their own development, this book explores the general process of how we make choices, from consciously rational to subconsciously emotional. Through exploratory lessons supplied in each chapter, kids learn the techniques of effective choice-making so that they have the tools to stand against outside sways. Special attention is given to instill in youth tools for positive and effective choices in both worlds they live in, "real life" and online"--